IMPLEMENTATION OF VALUE-ORIENTED MANAGEMENT IN NAVIGATION BUSINESSES - Jurkovic, Martin; Sosedova, Jarmila (Doprava a spoje, 2010)
Financial analysis based on modern value-oriented approaches to management brings new insights into the efficiency of a given business. It does not only offer the retrospective evaluation of the development of a company, it also provides a forecast of future performance, which makes it possible to fulfill company's strategic goals and long-term interest of its owners.